2016
DOI: 10.1128/jvi.00797-16
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Inhibits Kaposi's Sarcoma-Associated Herpesvirus Lytic Replication by Inducing MicroRNA miR-942-5p and Activating NF-κB Signaling

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) infection is required for the development of several AIDS-related malignancies, including Kaposi's sarcoma (KS) and primary effusion lymphoma (PEL). The high incidence of AIDS-KS has been ascribed to the interaction of KSHV and HIV-1. We have previously shown that HIV-1-secreted proteins Tat and Nef regulate the KSHV life cycle and synergize with KSHV oncogenes to promote angiogenesis and tumorigenesis. Here, we examined the regulation of KSHV latency by HIV-1 vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…HIV-1 Vpr inhibits KSHV lytic replication and induces pro-proliferative and -survival cytokines by inactivating Notch signaling. Our previous study has indicated that, following internalization into PEL cells, HIV-1 soluble Vpr protein inhibits KSHV lytic replication by activating NF-B signaling (23). Other studies have shown that KSHV can hijack the Notch signaling pathway to maintain the viral life cycle and determine the fate of adjacent cells (27,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 Vpr inhibits KSHV lytic replication and induces pro-proliferative and -survival cytokines by inactivating Notch signaling. Our previous study has indicated that, following internalization into PEL cells, HIV-1 soluble Vpr protein inhibits KSHV lytic replication by activating NF-B signaling (23). Other studies have shown that KSHV can hijack the Notch signaling pathway to maintain the viral life cycle and determine the fate of adjacent cells (27,31).…”
Section: Resultsmentioning
confidence: 99%
“…A cellular miR-711 directly targets Notch1 3=UTR. We have previously shown that soluble Vpr upregulates cellular miR-942-5p, which directly targets IB␣ 3= untranslated region (UTR) to inhibit KSHV lytic replication in PEL cells (23). To explore whether Notch signaling was also regulated by miRNAs during Vpr inhibition of KSHV lytic replication and induction of pro-proliferation and -survival cytokines, we analyzed previously identified Vpr-regulated miRNAs (23) using miRNA target prediction software, including PITA, RNA hybrid, and RNA22.…”
Section: Resultsmentioning
confidence: 99%
“…Since the KS lesion is of endothelial cell origin and HIV does not directly infect endothelial cells, studies have focused on elucidating the circulating soluble HIV proteins that may potentiate neoplastic processes (24)(25)(26)(27)(43)(44)(45). Previous reports indicated that viral proteins secreted by HIV-infected cells may be taken up by KSHV-infected cells and consequently dysregulate the KSHV latent to lytic infection switch (39,46) and promote disease progression (24-27, 43, 45). However, it should be note that KS tumor cells are almost exclusively latently infected (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…**, P Ͻ 0.01; ***, P Ͻ 0.005 (Student's t test). (39) or downregulated (8) by HIV Tat treatment upon KSHV reactivation, respectively. As shown in Fig.…”
Section: Fig 1 Legend (Continued)mentioning
confidence: 99%
“…Transfection was performed with 20 nM miRNA mimics using the Effectence Transfection reagent (Qiagen, Valencia, CA) following the manufacturer's instructions. Luciferase reporter assay was performed as previously described . Briefly, HEK293T cells (1 × 10 5 ) were co‐transfected with miRNA mimics, and Renilla vector pRL‐TK (Promega, Madison, WI) using Lipofectamine TM 2000 (Invitrogen, Carlsbad, CA) following the manufacturer's instructions, and then harvested at 24 h post‐transfection.…”
Section: Methodsmentioning
confidence: 99%